An Exploration of the Eductive Justifications of the Rational-Expectations Hypothesis - Guesnerie, Roger (American Economic Review, 1992)
This paper examines justifications of the rational-expectations hypothesis that rely on the analysis of the agents' mental forecasting ("educing") activity (which involves "forecasting the forecasts" of others, etc.). The corresponding concept of eductive learning stability, based on the game-theoretical concept of rationalizability, is primarily used within the classical Muth model. Conditions for coordination of beliefs are interpreted and discussed; they are robust to the introduction of noise. More generally, eductive stability fits economic intuition on coordination: stability increases when the industry product differentiation increases and when decisions are sequential and observable.